First principles model calculations of the biosynthetic pathway in selinadiene synthase. Issue 20 (15th October 2016) - Das, Susanta; Dixit, Mudit; Major, Dan Thomas
Graphical abstract: Abstract: Terpenes comprise the largest class of natural products currently known. These ubiquitous molecules are synthesized by terpene synthases via complex carbocationic reactions, incorporating highly reactive intermediates. In the current study, we present a mechanistic investigation of the biosynthetic pathway for the formation of selina-4(15), 7(11)-diene. We employ density functional theory to study a model carbocation system in the gas-phase, and delineate the energetic feasibility of a plausible reaction path. Our results suggests that during formation of selina-4(15), 7(11)-diene, the substrate is likely folded in a conformation conducive to sequential cyclizations. We propose that a required proton transfer cannot occur intramolecularly in the gas-phase due to a high free energy barrier, and that enzyme assistance is essential for this step. Hybrid quantum mechanics-molecular mechanics docking studies suggest that enzyme intervention could be realized through electrostatic guidance.